Prototype Sistem Kendali Keamanan Perlintasan Kereta Otomatis Menggunakan Gps Neo 6m - joni aditya (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2022)
Train transportation is the transportation that is often used by the community. Trains are in great demand by residents because of their safety. The method used in this research is experimental testing of gps parameters and using lora. The implementation process in this project tests parameters to detect passing trains. From the results of this study, several trials were carried out on the train. That is the trial of tracking from Tulungagung-Kediri and Kediri-Tulungagung. The goal is to determine the coordinates of the checkpoint points. Then test the transmitter and receiver. From the test results of the transmitter and receiver, the lora results that were tested on the train could only send 40 meter radius data. And the outdoor test got the results of the Los Lora point at a radius of 320 meters. The conclusion in this study should use lora which has higher specifications. And use an antenna whose transmit power reaches 30dbi